The relationship between perceived talent management practices, perceived organizational support (POS), perceived supervisor support (PSS) and intention to quit amongst Generation Y employees in the recruitment sector - Stanz, Karel J. (University of Pretoria, 2013)
Dissertation (MCom)--University of Pretoria, 2010.